CONCRETIONS WITH FOSSILS OF THE ULYANOVSK REGION - A NEW KIND OF JEWELRY-ORNAMENTAL RAW MATERIALS - D. A. Petrochenkov (Известия высших учебных заведений: Геология и разведка)
Concretions with fossils of the Ulyanovsk region are a new kind of jewelry and ornamental raw materials. Concretions are located in the middle part of the section of the Hauterivian sediments, which formed by dark gray dense clays. Concretions are dense, of dark gray or black colour, abundant with fragments of bivalves shells, less often with ammonites, and consist from, wt. %: calcite 85, aragonite 8, quartz 2, apatite 2, pyrite 2 and aluminosilicates 1. From the trace-elements there is Sr with a content of 0,08 wt. %. The contents of radioactive and carcinogenic elements are at background level. Aragonite constitutes the walls of the shells. Calcite is a cement of marl, and also constitutes fragments of shells. Pyrite constitute significant zones mainly in the outer parts of the concretions. In the central parts, it is presented as a rare dissemination. Quartz and aluminosilicates are minerals of bottom sediments. Calcite, apatite and pyrite are secondary minerals formed during the process of diagenesis of marine sediments. Contents of the trace-elements in calcite, wt. %, are: Mg from 0,52 to 2,19 and Mn from 0,34 to 2,13. There is no Fe, which is concentrated in pyrite. The structural features and chemical composition of minerals have been established. Concretions with fossils of the Ulyanovsk region are a technological high-decorative jewelry and ornamental material which allows producing of a wide range of jewelry and souvenirs.